Role of volume outcome data in assuring quality in HPB surgery - Langer, Bernard (2007)
Many studies have shown an association between both surgeon and hospital operative procedure volumes and outcomes, particularly operative mortality. It is also recognized that volume is only one of a number of factors, including 1) surgeon training and experience, and 2) hospital resources, organization, and processes of care, which can also influence outcomes. The Surgical Oncology Program at Cancer Care Ontario has included hospital volumes in a set of standards for the conduct of major pancreatic cancer surgery, along with recommendations for surgeon training and hospital resources, organization, support services, and processes of care to encourage regionalization of major HPB surgery. Cooperation with these recommendations was encouraged by the public reporting of mortality data and by an educational program directed at both surgeons and senior administrators in Ontario hospitals with the support of the provincial health ministry. The provincial mortality rate from major pancreatic cancer surgery has decreased by more than 50% since the introduction of this program.